PENGARUH PENGGUNAAN MEDIA BERBASIS ANDROID TERHADAP PENGETAHUAN BANTUAN HIDUP DASAR PADA MAHASISWA KEPERAWATAN - Bekti Sukoco; Widyandana Widyandana; Lutfan Lazuardi; Aris Setyawan (POLTEKKES KEMENKES JAYAPURA, 2020)
One of the student learning achievements in the emergency course is being able to carry out basic life support (BLS) procedures. With the development of mobile technology, mobile learning / m-learning is a potential for BLS learning. The purpose of this study was to determine the increase in student knowledge about BLS after using an android based application. Respondents in this study were 49 second year Bachelor of Nursing Students, STIKES Surya Global through simple random sampling. The method used to see student knowledge regarding the impact of using Android-based applications, using the onegroup pretest-posttest design pre-experimental approach. The result of this research is that there is an increase in BLS knowledge after using the AndroLifes application, because the benefits of smartphones are for learning and can strengthen knowledge, and smartphones are also proven to increase knowledge, so that it is widely used by students for learning because it contains complete content such as text, images, and audio-videos. It can be concluded that android-based applications can increase knowledge of BLS